Landmark judgments on election law 2017-19 - Election Commission of India (New Delhi Election Commission of India, 2020)
This edition of the series has departed from the format used in the previous books and judgements have been arranged based on subject matter. For the sake of convenience, a short description of each case has been given in the index itself and a tabular form of summaries has been provided before every judgement. Also, the indexes of the previous volumes have been added to this edition for easy reference. It also includes a list of all those cases, which came up during the process of general elections 2019 in various courts in the country.
Keywords: Election Law